Predictive role of cystatin C and increased proteinuria in early assessment of acute renal toxicity in patient poisoned by nephrotoxic drugs and poisons - Esam Mohammed Abdallah Ali; Emad Ahmad Mohamad Yousef; Maha Abd El-Hamed Helal; Mohammed Hamdi Mohammed; Meray Medhat Shokry Zaghary; Marwa Ahmed Hasb Elnabi (BMC Pharmacology and Toxicology)
Abstract Background Acute kidney injury (AKI) is prevalent in critical care, often due to nephrotoxic drug exposure, which accounts for significant morbidity and mortality. Current biomarkers, like serum creatinine, lack sensitivity for early detection of nephrotoxicity. Aim This study evaluates proteinuria and serum cystatin C as early indicators of nephrotoxicity in acutely poisoned patients at Sohag University Hospitals. Methods This prospective study involved 100 acutely poisoned patients with nephrotoxic effects admitted to Sohag University Hospitals from April to August 2021. Inclusion criteria required symptomatic patients who provided at least four blood or urine samples, including one within 24 h post-ingestion. AKI was classified using the Acute Kidney Injury Network (AKIN) criteria, with baseline serum creatinine estimated from the lowest value during hospitalization. Biomarkers, including serum creatinine and cystatin C, were measured using standard assays for analysis. Results The study included 100 patients aged 2 to 58 years, predominantly male (72%). Most participants were from rural areas (82%). Serum creatinine levels significantly increased from day 1 (mean ± SD: 1.67 ± 0.6 mg/dL) to day 2 (mean ± SD: 2.98 ± 1.35 mg/dL). Significant predictors of acute renal toxicity included serum creatinine on both days (P < 0.001), proteinuria ACR (P = 0.023), and cystatin C (P < 0.001). Cystatin C had the highest predictive value (AUC = 0.993), while proteinuria ACR and day 2 serum creatinine showed significant predictive capabilities (AUCs of 0.805 and 0.873, respectively). Conclusion In conclusion, proteinuria and cystatin C are reliable predictors for early nephrotoxicity detection in acutely poisoned patients at Sohag University Hospitals. These biomarkers effectively indicate and assess the severity of kidney injury caused by toxicity.